Örgütsel İkiyüzlülük Alanının Haritalandırılması: Bibliyometrik Bir Analiz. - Oruç, Şükran; Orçanlı, Kenan (Itobiad: Journal of the Human & Social Science Researches / İnsan ve Toplum Bilimleri Araştırmaları Dergisi, 2026)
The phenomenon of organizational hypocrisy, defined as the discrepancy between an organization's rhetoric and its actual practices, has emerged as a critical field of study due to its profound impact on stakeholder trust, corporate reputation, and employee engagement. This study aims to delineate the intellectual landscape of the organizational hypocrisy literature by conducting a bibliometric analysis of its development between 1999 and 2025. A total of 301 publications, curated from the Web of Science Core Collection and Scopus databases, were subjected to a two-stage analytical process using the Python programming language. The research findings indicate that while scholarly interest in organizational hypocrisy remained limited for many years, it gained significant momentum after 2020, reaching a historical peak in 2025. This systematic growth confirms that the subject has transcended transient curiosity to become a permanent academic discipline. An examination of the field's primary focal points reveals a clustering around strategic themes such as corporate social responsibility (CSR) and sustainability, alongside micro-psychological dimensions including employee trust and ethical perception. While concepts such as corporate performance and perceived sincerity constitute the "motor themes" of the current literature, areas such as governance and transparency are identified as emerging domains. Geographically, China and the United Kingdom stand out as primary hubs of knowledge production, yet the international collaboration network has not yet reached full maturity. The fact that a vast majority of contributors have authored only a single study suggests that while the field attracts broad interest, a highly specialized and consolidated author base is still in the process of formation. Total citation counts and scientific impact metrics demonstrate that the literature on organizational hypocrisy has attained a reputable and influential status within the global academic community. Future research is recommended to focus on multi-level approaches integrating corporate strategies with individual perceptions, sincerity patterns in ESG reporting, and the emerging role of artificial intelligence in shaping organizational transparency.